MEREK SEBAGAI PENDORONG KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MAKE OVER DI KOTA BLITAR - Denok Wahyudi Setyo Rahayu (Universitas Islam Balitar, 2018)
Consumer behavior has become a consumer habit in shopping. This affects the pattern of product purchasing decision. The purpose of the study was to find out whether the brand could be a driver of buying Make Over cosmetics product in the city of Blitar. The variables used are brands and purchasing decisions with samples of seller and buyers of Make Over cosmetic product in the city of Blitar. The resut of the study found that cosmetics brands Make Over became the driving force for purchasing cosmetic products in the city of Blitar.